Do intensive guidance programs reduce social inequality in the transition to higher education in Germany? Experimental evidence from the ZuBAb study 0.5 years after high school graduation - Melinda Erdmann; Irena Magdalena Pietrzyk; Marcel Helbig; Marita Jacob; Stefan Stuth (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2022)
This paper examines the effect of an intensive counseling program to promote university access among students who are eligible for university. Using data from the experimental panel study ZuBAb, we examine the average effect on university enrollment directly after high school graduation and the effect heterogeneity by educational background. No positive effect of participation is found. We discuss these results in relation to the potential of reducing inequalities through individual counseling in Germany. – – Im Beitrag wird die Wirkung eines intensiven Beratungsprogramms zur Förderung der Studienaufnahme von Hochschulzugangsberechtigten untersucht. Mittels Daten aus der experimentellen Panelstudie ZuBAb werden der durchschnittliche Effekt auf die Studienaufnahme direkt nach dem Abitur und die Effektheterogenität nach Bildungsherkunft überprüft. Es zeigt sich keine positive Wirkung der Teilnahme. Diese Ergebnisse werden in Bezug auf die ungleichheitsreduzierenden Potentiale individueller Beratung in Deutschland diskutiert.
Keywords: 300; university access; educational intervention; experiment; social origin; Studienaufnahme; Bildungsintervention; Experiment; soziale Herkunft